Strategies to encourage positive organizational citizenship behavior - Pramono, Galih Panjalu; Sari , Yane Puspito (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to increase employee commitment, especially to organizational values at one of the public high schools in the Semarang Alumni Association, with the hope of increasing Organizational Citizenship Behavior (OCB) which supports school goals. The focus of the research involves analyzing factors that influence OCB, particularly job stress and organizational commitment. Empirical research methods using data collection through surveys and statistical analysis are used. The research results show that work stress negatively influences the level of individual commitment to the organization, while organizational commitment has a significant positive impact on OCB. It was found that organizational commitment acts as a mediating variable in the relationship between job stress and OCB. Research recommendations include stress management, developing organizational commitment, and increasing organizational citizenship behavior to create a healthy work environment and support the development of positive OCB.